Addressing the mental health needs of India’s aging population: Understanding depression prevalence and social risk factors in tertiary care outpatients - Joanne Lydia Rajkumar; Surekha Viggeswarapu; Suja Kurian; Munaf B. Nandyal; Mahasampath Gowri (Indian Journal of Psychiatry)
Background: Depression is a major public health problem among older persons. Identifying the prevalence and recognizing modifiable risk factors of depression in older persons is essential for early diagnosis and appropriate management. Apart from traditional risk factors, medical comorbidities, chronic illness, and social factors can contribute to depression in the older person. This study aimed to estimate the prevalence of depression and identify the medical and social risk factors associated with depression in older persons attending a geriatric outpatient clinic. Methods: Consecutive patients aged over 60 years presented to the geriatric outpatient clinic of the Christian Medical College (CMC) and Hospital, Vellore, were screened using the Physical Health Questionnaire-2 (PHQ-2) and Geriatric Depression Scale (GDS). Medical, social, and financial information were collected. Following a detailed clinical interview, the Clinical Interview Schedule-Revised (CIS-R) was administered and the ICD-10 diagnosis of depression was derived. Results: A total of 171 participants were recruited. The prevalence of depression was found to be 53.2% with PHQ-2 and 35.6% with GDS. Using CIS-R, 41.5% had an ICD-10 diagnosis of depression. The risk factors associated with depression in older persons were female gender, financial insecurity, lack of pension, and financial dependence. Conclusion: This study revealed a high prevalence of depression among older persons attending a geriatric outpatient clinic. Financial insecurities, particularly lack of pension or financial dependence, were identified as significant social risk factors for depression. Addressing these risk factors may help prevent the onset or progression of depression, thus improving their quality of life.